Interpersonal process in psychotherapy a relational approach - Teyber, Edward (Australia Belmont, CA Brooks/Cole, 2000)
"In this book, experienced educator and clinician Edward Teyber shows beginning therapists how to use the relationships they establish with their clients to help clients change. Teyber includes therapeutic goals and intervention strategies for each phase of treatment and has organized the book to parallel the course of treatment from initial client contact to termination. Interpersonal Process in Psychotherapy: A Relational Approach brings together basic skills, case formulations, and intervention strategies with real clients in real settings. Current and updated throughout, this Fourth Edition includes the realistic challenges of managed care practice, helping counselors to develop a treatment focus and formulate intervention plans; even fuller integration of cognitive-behavioral, family-systems, and interpersonal/dynamic approaches; structured step-by-step presentation of essential clinical concepts for even greater clarity; illustrative case studies that develop multicultural awareness in every chapter; and numerous clinical vignettes, sample therapist-client dialogues, and extended case studies."--BOOK JACKET.
Introduction and overview -- Establishing a working alliance -- Honoring the client's resistance -- An internal focus for change -- Responding to conflicted emotions -- Familial and developmental factors -- Inflexible interpersonal coping strategies -- Current interpersonal factors -- An interpersonal solution -- working through and termination -- Appendix A: Process notes -- Appendix B: Case formulation guidelines.
Includes bibliographical references (p. 313-318) and indexes.
Keywords: Psychotherapist and patient; Psychotherapy; Psychotherapy -- methods; Interpersonal Relations; Physician-Patient Relations